Is Radical Surgery Alone Enough in T1-3N1a Colon Cancer? - Xu, Guoxiong; Jin, Yiqi; Fang, Changwen; Yu, Jingfan; Zhang, Zhixuan; Sun, Chunrong (Frontiers in Oncology, 2020)
Background: Low lymphatic tumor burden would be associated with better prognosis, however, it still remained uncertain whether those clinically node negative colon cancer found to be pathologically diagnosed with node involvement could be a favorable subgroup in stage III disease and could be treated with radical surgery alone to avoid overtreatment. Methods: Eligible patients diagnosed with colon cancer without metastasis were recruited from Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2016 using SEER*Stat 8.3.5 software (Surveillance Research Program, National Cancer Institute) and divided into two groups: surgery group (n = 3081) and surgery and adjuvant chemotherapy group (n = 4591). Overall survival (OS) and cause-specific survival (CSS) differences were assessed by Kaplan–Meier analysis, and survival differences were estimated with log-rank tests. Univariate and multivariate Cox proportional hazard regressions were used to assess hazard ratios (HRs) and 95% confidence intervals (CIs) for colon cancer patients. Results: A total of 7672 pT1-3N1a colon cancer patients meeting with strict inclusion criteria of our analyses were recruited from 208751 colon cancer patients. The 5-year CSS rates of patients without adjuvant chemotherapy and patients with adjuvant chemotherapy were 80.0% and 90.7%, respectively. The receipt of adjuvant chemotherapy after the radical resection of the primary tumor was independently associated with 57.3% decreased risk of colon cancer-specific mortality compared with surgery alone (HR = 0.427, 95%CI = 0.370-0.492, P < 0.001, using surgery alone as the reference). Conclusions: Adjuvant chemotherapy was significantly associated with improved prognosis and radical surgery alone was not enough in colon cancer with very low lymphatic tumor burden.